2022
DOI: 10.15835/nbha50312969
|View full text |Cite
|
Sign up to set email alerts
|

Commercial and phytochemical quality in biofortified ‘Orejona’ lettuce with zinc oxide nanoparticles

Abstract: Crop biofortification is a recent strategy based on the production of plants rich in micronutrients for human consumption. The biofortification of plants with minerals is considered one of the least expensive and most efficient ways to improve the commercial and nutritional quality of horticultural products, in addition to improving crop yields. The objective of the research was to evaluate commercial and phytochemical quality, physiological parameters, and zinc concentration in lettuce leaves (Lactuca sativa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…In our study, we found significant differences in antioxidant capacity (DPPH method) as a result of the application of ZnO NPs. This mean that the antioxidant capacity may depend on the abundance of metal ions as it has been reported in previous studies (Sida-Arreola et al, 2017;Preciado-Rangel et al, 2021;Fortis-Hernández et al, 2022;.…”
Section: Discussion Discussion Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In our study, we found significant differences in antioxidant capacity (DPPH method) as a result of the application of ZnO NPs. This mean that the antioxidant capacity may depend on the abundance of metal ions as it has been reported in previous studies (Sida-Arreola et al, 2017;Preciado-Rangel et al, 2021;Fortis-Hernández et al, 2022;.…”
Section: Discussion Discussion Discussionsupporting
confidence: 58%
“…Our results are similar with those reported for other researchers who found that phenolic content of plants was significantly enhanced by application of ZnO NPs fertilizers. For example, in basil plant (Abbasifar et al, 2020), in orejona lettuce (Fortis-Hernández et al, 2022) and habanero pepper (García-López et al, 2018).…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%